A technique engineered for improving thermal conductive properties of polyamide-6 composites via hydroxylated boron nitride masterbatch-based melt blending. (1st May 2021) - Guo, Hanyin; Xu, Tongle; Zhou, Shuaishuai; Jiang, Fang; Jin, Liyuan; Song, Na; Ding, Peng
Abstract: Thermal conductive and electrical insulating polymer composites are showing tremendous potential for modern electrical systems and electronic devices. Melt blending has been utilized as an effective technique to prepare thermal interface materials. However, during the process of melt-blending, strong π-π stacking and particle aggregation may be caused by thermal heating and local mechanical stress. Herein, ISP-PA6/BNNSs-OH (ISP-PN) composite has been fabricated by a masterbatch obtained via in-situ polymerization (ISP) and melt blending with polyamide-6 (PA6), with the incorporation of hydroxylated boron nitride nanosheets (BNNSs-OH). At the filler loading of 10 wt%, the through-plane thermal conductivity (TC) and Young's modulus of ISP-PN composites are respectively increased by 163% and 118%, compared to that of the neat PA6 resin. Prevailing over the matrix, the ISP-PN composites own volume electrical resistivity of ~5.11 × 10 19  Ω cm. Meanwhile, the TC and mechanical properties of ISP-PN composites are 21.4% and 28.0% higher than the composites obtained by direct melt blending. The improved properties are attributed to the pre-disperse of filler through the masterbatch method. The PA6 chains were immobilized onto the BNNSs-OH by the condensation reaction, resulting in a sort of "chain-extender" and preventing the filler from re-aggregating during the process of melt-blending. This study pioneers a simple and versatile path to melt blending of thermally conductive polymer composites with good mechanical and electrical insulation properties in high-performance thermal management systems.